Expression of p16 and pKi-67 in cervical preneoplasia and neoplasia - Looi, Mee-Lee; Ahmad Zailani Hatta Mohd Dali; Siti Aishah Md. Ali; Yasmin Anum Mohd Yusof (UKM Medical Molecular biology Institute, UMBI, 2011)
This study was conducted to investigate the expression of p16 and pKi-67 in normal, preneoplasia and neoplasia lesions of the uterine cervix. One hundred and thirty one cervical specimens, consisting of normal cervix (n = 43), cervical intraepithelial neoplasia (CIN) lesions (n = 40) [16 LSIL: CIN 1 and 24 HSIL: 9 CIN 2 and 15 CIN 3] and cervical squamous cell carcinomas (n = 48) [16 SCC I, 17 SCC II, 7 SCC III and 8 SCC IV] were examined immunohistochemically in paraffin sections. All samples of the normal cervix were negative for p16. Immunoreactivity of p16 was observed in 4/ 16 LSIL, 12/24 HSIL and 30/48 SCC. In all p16-positive samples, both nuclear and cytoplasmic staining were observed. High expression of p16 (> 50 % of cell stained) was found in HSIL and SCC. Ki-67 index was significantly (p < 0.05) higher in high-grade squamous intraepithelial lesions (HSIL: CIN 2 & 3) and SCC lesions when compared to normal cervices. The expression of p16 and Ki-67 proliferation profile (< or > 30 % stained cells) were significantly associated with the grade of lesions (χ2 = 6.832, p = 0.033 and χ2 = 10.952; p = 0.012 respectively). There was no significant relationship demonstrated between p16 positivity and Ki-67 proliferation profile (χ2 = 0.292; p = 0.589). Our results indicated that p16protein may be involved in the carcinogenesis of cervical cancer. However, overexpression of p16 seemed to have no effect on cell proliferation. The expression of p16 and pKi-67 may be useful in cases where it is difficult to make a diagnosis by histology.